2019
DOI: 10.3390/su11071959
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Linear Effect of Financial Support on Energy Efficiency: Evidence from China

Abstract: This study examines the non-linear effect of financial support on energy efficiency for 30 provinces in China, over the period 2003 to 2016. Specifically, we find that technological progress is a key factor in improving energy efficiency, regardless of the transition variable or sample chosen. The non-linear effects of the support of different financial sectors on energy efficiency are different. Banks have the greatest positive impact on energy efficiency, but as economic and financial development levels incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Therefore, this study sheds light on the view that the targeted poverty alleviation efforts of firms can reduce their cost of equity capital in the presence of private property nature. In addition, the differences between regions are similar to those described in a previous study [57]. Due to the uneven development and information environment, the relationship between poverty alleviation participation and the cost of equity capital is not significant in the west region.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, this study sheds light on the view that the targeted poverty alleviation efforts of firms can reduce their cost of equity capital in the presence of private property nature. In addition, the differences between regions are similar to those described in a previous study [57]. Due to the uneven development and information environment, the relationship between poverty alleviation participation and the cost of equity capital is not significant in the west region.…”
Section: Discussionsupporting
confidence: 80%
“…Accordingly, the process by which information is conveyed and interpreted by investors may vary in different regions. We divide the whole sample into three groups, that is, the eastern, central and western regions [57], respectively, to test the impact of enterprises' poverty alleviation engagement on the cost of equity capital in these three regions, and the results are shown in column 2 of Table 7.…”
Section: The Impact Of Property Nature Region and Mandatory Disclosurementioning
confidence: 99%
“…Analysis of the contribution of authors (Fig. 5) showed that the leading positions belong to scientists from Taiwan [50,51] in third place are scientists from Australia.…”
Section: Fig 5 Contribution Of Individual Scientists In the Field Of Green Competitiveness Research Source: Composed By The Authors Basedmentioning
confidence: 99%
“…Nonlinear effects are widespread in the recent study [38][39][40][41]. e PSTR model can accurately describe the transition between the linear and nonlinear models in the process of energy intensity by selecting different transition variables or transfer functions [42,43]. e PSTR model may be considered as a linear heterogeneous panel model, which allows regression coefficients to vary across individuals and over time.…”
Section: Panel Smooth Transition Regression Modelmentioning
confidence: 99%